Mathematics
adcampy18
2016-04-14 06:41:51
Find the sum of a finite geometric sequence from n = 1 to n = 8, using the expression −2(3)^n − 1.
ANSWERS
DanaeConey
2016-04-14 11:23:50

The sum if the geometric sequence given by: an=-2(3)^(n-1) will be: when: n=1 an=-2 when n=2 a2=-6 when n=3 a3=-18 when n=4 a4=-54 when n=5 a5=-162 when n=6 a6=-486 when n=7 a7=-1458 when n=8 a8=-4374 thus the summation of the term will be: Sn=(-4374+-1458+-486+-162+-54+-18+-6+-2) Sn=-6560 the answer is -6560

ADD ANSWER